The cost of cooking for foragers. Issue 162 (January 2022) - Magargal, Kate
Abstract: Cooked food provides more calories to a consumer than raw food. When our human ancestors adopted cooking, the result was an increase in the caloric value of the diet. Generating the heat to cook, however, requires fuel, and accessing fuel was and remains a common problem for humanity. Cooking also frequently requires monitoring, special technology and other investments. These cooking costs should vary greatly across multiple contexts. Here I explain how to quantify this cooking trade-off as the ratio of the energetic benefits of cooking to the increased cost in handling time and examine the implications for foragers, including the first of our ancestors to cook. Ethnographic and experimental return rates and nutritional analysis about important prey items exploited by ethnohistoric Numic foragers in the North American Great Basin provide a demonstration of how the costs of cooking impact different types of prey. Foragers should make choices about which prey to capture based on expectations about the costs involved to cook them. The results indicate that the caloric benefit achieved by cooking meat is quickly lost as the cost of cooking increases, whereas many plant foods are beneficially cooked across a range of cooking costs. These findings affirm the importance of plant foods, especially geophytes, among foragers, and are highly suggestive of their importance at the onset of cooking in the human lineage.